STUDI KEPUASAN KARYAWAN DENGAN PENGARUH MOTIVASI, PENGEMBANGAN KARIR DAN LINGKUNGAN KERJA DI PT SOLO GARMINDO - Andri Yuwono; Andhi Supriyadi (LPSDI Bina Patria, 2025)
This research was conducted at PT Solo Garmindo with the aim of evaluating the impact of motivation, career development and a non-optimal work environment. The information sought in the research was collected through the use of questionnaires and interviews. 110 respondents were used in the study. It is hoped that this research will provide useful information for management and employees. The information obtained is processed by The use of multiple regression for quantitative analysis is used to understand how the independent variable affects the dependent variable, as well as to test models and hypotheses, while also checking validity and reliability. Regression observations show that motivation, career development, and work environment have a direct impact on increasing job satisfaction. Thus, increased motivation, sustainable career development and a good work environment are needed to increase employee job satisfaction in the future.